An NDN based indoor positioning and navigation system - Taki, Sifat Ut; Hossain, Raiyan; Anwar, Sadia (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.